Sex Difference in Plasma Deoxyribonuclease Activity in Rats - Janovičová, Ľubica; Gromová, Barbora; Drobná, Diana; Konečná, Barbora; Domonkos, Emese; Borbélyová, Veronika; Hodosy, Július; Celec, Peter (Physiological research, 2021)
Extracellular DNA (ecDNA) activates immune cells and is involved in the pathogenesis of diseases associated with inflammation such as sepsis, rheumatoid arthritis or metabolic syndrome. DNA can be cleaved by deoxyribonucleases (DNases), some of which are secreted out of cells. The aim of this experiment was to describe plasma DNase activity in relation to extracellular DNA in adult rats, to analyse potential sex differences and to prove whether they are related to endogenous testosterone. Adult Lewis rats (n=28) of both sexes were included in the experiment. Male rats were gonadectomized or sham-operated and compared to intact female rats. Plasma ecDNA and DNase activity were measured using fluorometry and single radial enzyme diffusion assay, respectively. Concentrations of nuclear ecDNA and mitochondrial ecDNA were determined using real-time PCR. Females had 60% higher plasma DNase activity than males ( p=0.03). Gonadectomy did not affect plasma DNase in males. Neither the concentration of total ecDNA, nor nuclear or mitochondrial DNA in plasma differed between the groups. No significant correlations between DNase and ecDNA were found. From previous studies on mice, it was expected, that male rats will have higher DNase activity. In contrast, our study in rats showed the opposite sex difference. This sex difference seems not to be caused by endogenous testosterone. Interestingly, no sex differences were observed in plasma ecDNA suggesting a complex or missing association between plasma ecDNA and DNase. The observed sex difference in plasma DNase should be taken into account in animal models of ecDNA-associated diseases.
Keywords: testosteron; Animals; Sex Characteristics; potkani inbrední LEW; Testosterone; DNA; orchiektomie; Female; zvířata; mužské pohlaví; Deoxyribonucleases; Male; Orchiectomy; Rats, Inbred Lew; deoxyribonukleasy; pohlavní dimorfismus; ženské pohlaví